On the Polish-Slovak relations 1938–1939 (Theatrum historiae, 2015)
This article deals with Slovakia in 1938–1939 in an international context as an object of diplomatic issues between Poland, the Third Reich and Hungary. Author presents the evolution of the problem of autonomy and independence of Slovakia and its place in the politics of neighbouring countries with particular emphasis on Polish politics. The article shows the reasons of the anti-Polish Slovak politics in 1939.
Keywords: Central Europe; Poland; Slovakia; international relations; 1938–1939